A Prediction Model Based on the Long Electrode Source for Fault Anomaly in Tunnel - Daiming Hu; Hao Liu; Xiaodong Yang; Mingxin Yue (Geofluids)
The resistivity method has been widely used to predict the water-bearing structure of tunnels. The traditional resistivity uses the point electrode (PE) source in the tunnel to excite the electric field. Because the tunnel face is inaccessible, its exploration depth is limited and small. In order to overcome this problem, the horizontal pilot hole is used as the long electrode (LE) source in the tunnel. We use the finite element method (FEM) to establish a three-dimensional modeling algorithm for tunnel detection using a long electrode source. The accuracy of the algorithm is verified by using the long electrode source model. By a lot of numerical simulations, a prediction model of a long electrode source for tunnel detection is firstly proposed. The predicted results show that it has good applicability in detecting long-distance anomaly. The comparison of the long electrode source and point electrode source models shows that the detection depth of the long electrode prediction model is farther than that of the point electrode source. This long electrode source method can improve the construction efficiency and effectively prevent water inrush in the tunnel.